2019
DOI: 10.1007/s10433-019-00499-w
|View full text |Cite
|
Sign up to set email alerts
|

Defining organizational contributions to sustaining an ageing workforce: a bibliometric review

Abstract: The ageing of populations worldwide has implications for workforces in developed countries and labour shortages have increasingly become a political concern. Governments in developed countries have responded by increasing the retirement age as a strategy for overcoming the fall in labour supply. Using bibliometric techniques, we reviewed 122 articles published between 1990 and 2018 to examine the effectiveness of the strategy in addressing the labour shortages and, in particular, to identify the factors that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 101 publications
0
23
0
Order By: Relevance
“…During the last few decades, pension reforms have been carried out all over Europe, meaning that workers have to work more years in order to overcome the issue of labor shortages and a rise in government costs [39]. Some researchers have suggested that this could lead to a decline in the productivity level of older workers, as their muscular strength is expected to decrease due to the aging process [40], especially in those individuals engaged in physically demanding occupations, such as PTs.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades, pension reforms have been carried out all over Europe, meaning that workers have to work more years in order to overcome the issue of labor shortages and a rise in government costs [39]. Some researchers have suggested that this could lead to a decline in the productivity level of older workers, as their muscular strength is expected to decrease due to the aging process [40], especially in those individuals engaged in physically demanding occupations, such as PTs.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in many fields, including for example, economics and management, have focused on investigating the impacts of an aging workforce (Börsch-Supan, 2000; Kulik et al, 2014; Vasconcelos, 2015). In the HRM literature several researchers propose that organizations can take advantage of their new age structure through HR practices and policies (e.g., Kooij et al, 2008; Truxillo et al, 2015; Nagarajan et al, 2019). Previous research challenged the universality of HRM showing that work-related motives and attitudes change with age, and that there are HR practices that can especially fit older workers’ needs and preferences (Ng and Feldman, 2010; Armstrong-Stassen and Schlosser, 2011; Kooij et al, 2011; Pinto et al, 2014; Kim and Kang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers believe that without defining and addressing the challenges faced by older workers, any policy that increases the retirement age will be ineffective in overcoming the economic development consequences of an aging population (Nagarajan et al, 2019). Therefore, in the following subsection, we identify and discuss the challenges of retaining older workers in the workforce.…”
Section: The Significance Of the Demographic Transitionmentioning
confidence: 99%
“…Aging workers are also an incredibly rich resource, given their valuable skill sets, experience, and commitment, and their ongoing involvement in the workforce is expected to increase overall national productivity . However, the reality of retaining senior workers in the workforce can be difficult because they are often challenged by health issues and out-of-date technological knowledge (Nagarajan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation